The Governance Advocacy of Indonesian Civil Society to Supporting Palestinian Rights - Umar, Alya Khasuna; Nur Azizah (Jurnal Studi Pemerintahan, 2025)
Israel’s massive attacks on public facilities, places of worship, and hospitals in Palestine that have been going on since October 2023 have raised global community solidarity to fight Israel by all means, including by carrying out Boycott, Divestment, and Sanctions (BDS) against products affiliated with Israel. This article aims to explain “Why does the BDS Movement gain widespread support from the Indonesian people to understand this phenomenon, a qualitative descriptive research method was used. Research data were obtained through literature studies of reputable journals published in Scopus and Sinta. Other secondary data were obtained from the official website of the BDS Movement, the Indonesian Ministry of Foreign Affairs, and digital news. Primary data were obtained from observations at various McDonald’s and KFC outlets, as well as interviews with several students of elementary school in Yogyakarta. The analysis will be conducted using the Transnational Advocacy Network framework from Margareth Keck and Kathryn Sikkink. The findings of this study indicate that the BDS Movement has gained widespread support in Indonesia because Israel’s actions in committing genocide and colonization of the Palestinian people have violated the principles of humanity stated in the Pancasila and the 1945 Constitution. The BDS Movement is also in line with the Foreign Policy of the Republic of Indonesia which consistently supports the independence of the Palestinian people. The BDS Movement uses social media and mass media as a means of “information politics” so that it has succeeded in raising awareness, social concern and solidarity actions of Indonesian.